Pacific Decadal Oscillation Modulates the Relationship Between Pacific Meridional Mode and Tropical Cyclone Genesis in the Western North Pacific. Issue 5 (8th March 2023) - Wang, Chao; Fu, Meiling; Wang, Bin; Wu, Liguang; Luo, Jing‐Jia
Abstract: Pacific Meridional Mode (PMM) is known to be significantly correlated with tropical cyclone (TC) genesis over the western North Pacific (WNP), while the stability of their relationship remains unknown. Here we found that their relationship is nonstationary, which depends on the phase of Pacific Decadal Oscillation (PDO). During the PDO warm phases, the PMM‐emanated cyclonic circulation and ascending motion can propagate to the entire WNP due to the enhanced background convection. In contrast, during the PDO cold phases, the PMM‐resulted cyclonic circulation and ascending motion are confined to the eastern WNP, while the compensated descending motion prevails in the western WNP. Accordingly, the PMM‐induced consistent (inconsistent) changes in large‐scale conditions across the western and eastern WNP act to strengthen (weaken) the relationship between the PMM and WNP TC genesis during the PDO warm (cold) phases. The result provides further guidance for improving seasonal prediction of TC genesis. Plain Language Summary: Billions of people in the Pacific islands and Asian coastal regions are subject to enormous tropical cyclone (TC) induced disasters. The Pacific Meridional Mode (PMM), a seasonally evolving mode of coupled climate variability, has a prominent impact on TC genesis in the western North Pacific (WNP) and is usually used as an important predictor for seasonal forecasting of TC genesis. However, stability in the relationship between PMM and TC genesis remains unclear. Here we found that their relationship is nonstationary and depends on the phase of the Pacific Decadal Oscillation (PDO), a decadal fluctuation of the Pacific Ocean. The result highlights the crucial role of PDO in modulating the relationship between the PMM and WNP TC genesis and thus provides further guidance for seasonal forecasting scheme of TC genesis. Key Points: The relationship between the Pacific Meridional Mode (PMM) and tropical cyclone genesis over the western North Pacific is nonstationary The nonstationary relationship stems from the diverse atmospheric responses to PMM that depend on the phase of Pacific Decadal Oscillation